A glimpse of history: non-intubated thoracic surgery - Tamburrini, Alessandro; Mineo, Tommaso Claudio (Video-Assisted Thoracic Surgery, 2017)
Thoracic surgeons in the modern era are expected to push the limits of their performances, limiting the invasiveness of operations and minimizing harm to the patients, keeping safety as the very first priority and benefiting from the constant scientific advances and technological developments. Minimally invasive thoracic surgery performed without use of general anesthesia, which seems to be the “end product” of this era, conveys instead a long, fascinating history of evolutions and revolutions. After World War I, the already established practice of chest operations on awake patients was furtherly implemented, reaching a peak in the 1950s when significant refinements in regional anesthesia techniques allowed pioneer surgeons to perform major thoracic procedures in spontaneously ventilating patients under epidural analgesia or by carefully developed multi-step nerve blocks. The introduction as a standard of practice of double-lumen endotracheal tube limited further developments in open surgery, but did not stop the ongoing evolution of thoracoscopy, the very first minimally invasive approach to the chest. Invented and popularized in the 1910s, thoracoscopy in awake patients for diagnostic and therapeutic purposes gained conversely widespread acceptance after the 1950s. It was extensively performed in most cases under local anesthesia and it can be rightfully considered the closest progenitor of modern minimally-invasive non-intubated surgery. The compelling affirmation on a large scale of video-assisted thoracic surgery (VATS) was the real game-changer in the 21st century, giving birth to a whole new idea of minimally-invasive. Shortly after its introduction though, the new pioneers in surgery developed a novel concept of “non-intubated” and “awake” thoracoscopic procedures, which are being continuously refined and implemented. From a dedicated investigational research program on “non-intubated” thoracic surgery, to complex chest operations under “non-general” anesthesia and to uniportal “tube-less” lobectomy, history of surgery is an ongoing and fascinating event, and past, present and future generations of thoracic surgeons are all part of it.